Identification of ASYNAPTIC4, a Component of the Meiotic Chromosome Axis. Issue 1 (12th July 2018) - Chambon, Aurélie; West, Allan; Vezon, Daniel; Horlow, Christine; De Muyt, Arnaud; Chelysheva, Liudmila; Ronceret, Arnaud; Darbyshire, Alice; Osman, Kim; Heckmann, Stefan; Franklin, F. Chris H.; Grelon, Mathilde
Abstract : ASYNAPTIC4 is required for normal meiotic recombination and synapsis in Arabidopsis thaliana. Abstract: During the leptotene stage of prophase I of meiosis, chromatids become organized into a linear looped array via a protein axis that forms along the loop bases. Establishment of the axis is essential for the subsequent synapsis of the homologous chromosome pairs and the progression of recombination to form genetic crossovers. Here, we describe ASYNAPTIC4 (ASY4), a meiotic axis protein in Arabidopsis ( Arabidopsis thaliana ). ASY4 is a small coiled-coil protein that exhibits limited sequence similarity with the carboxyl-terminal region of the axis protein ASY3. We used enhanced yellow fluorescent protein-tagged ASY4 to show that ASY4 localizes to the chromosome axis throughout prophase I. Bimolecular fluorescence complementation revealed that ASY4 interacts with ASY1 and ASY3, and yeast two-hybrid analysis confirmed a direct interaction between ASY4 and ASY3. Mutants lacking full-length ASY4 exhibited defective axis formation and were unable to complete synapsis. Although the initiation of recombination appeared to be unaffected in the asy4 mutant, the number of crossovers was reduced significantly, and crossovers tended to group in the distal parts of the chromosomes. We conclude that ASY4 is required for normal axis and crossover formation. Furthermore, our data suggest that ASY3/ASY4 are the functional homologs of the mammalian SYCP2/SYCP3 axial components.